دراسة تأثير تطورات أسعار البترول على الإنفاق العام دراسة قياسية لحالة الجزائر الفترة الممتدة بين (1990-2022) - أحمد بن نايهة (My University, 2024)
This study aims to investigate the impact of oil price fluctuations on government spending in Algeria. The researchers employed a standard methodology using autoregressive distributed lag (ARDL) approach applied to annual time series data of government spending and oil prices from 1990 to 2022. The data for oil prices were obtained from the Energy Information Administration (EIA) website, while the government spending data relied solely on the World Bank's World Development Indicators (WDI). The study found evidence of a long-term equilibrium relationship between oil prices and government spending. This suggests that government spending in Algeria is closely linked in the long run to changes in oil prices. Since this relationship is causal and significant, government spending in Algeria expands during periods of rising oil prices and contracts during periods of falling oil prices in the long run. In the short term, there is a causal relationship between oil prices and government spending. تهدف هذه الدراسة إلى معرفة مدى تأثير تقلبات أسعار النفط على الإنفاق الحكومي في الجزائر وذلك من خلال دراسة قياسية استخدمنا فيها منهجية الانحدار الذاتي للفجوات الزمنية الموزعة طبقت على سلاسل زمنية سنوية لكل من الإنفاق الحكومي وأسعار النفط من سنة 1990 إلى 2022 ، وفيما يتعلق بالبيانات التي بنيت عليها الدراسة فقد تحصلنا على بيانات أسعار النفط من موقع إدارة معلومات الطاقة EIA ، أما فيما يخص سلسلة بيانات الإنفاق الحكومي فقط اعتمدنا على بيانات البنك الدولي WDI . وقد خلصت الدراسة إلى وجود علاقة توازنية طويلة الأجل بين أسعار النفط والإنفاق الحكومي، وهو ما يعني بأن الإنفاق الحكومي في الجزائر يرتبط في المدى البعيد ارتباطا وثيقا بتغيرات أسعار النفط، وبما أن أن هذه العلاقة طردية ومعنوية فإنه في المدى البعيد تتوسع سياسة الإنفاق الحكومي في الجزائر في الفترات التي ترتفع فيها أسعار النفط وتنكمش في الفترات التي تنخفض فيه أسعار النفط، أما في الأجل القريب توجد علاقة طردية معنوية بين أسعار النفط والإنفاق الحكومي. Cette étude vise à examiner l'impact des fluctuations des prix du pétrole sur les dépenses publiques en Algérie, en utilisant une approche méthodologique de régression à effets fixes appliquée aux séries temporelles annuelles des dépenses publiques et des prix du pétrole de 1990 à 2022. Les données sur les prix du pétrole ont été obtenues auprès de l'Energy Information Administration (EIA), tandis que les données sur les dépenses publiques proviennent de la Banque mondiale (WDI). L'étude a conclu à l'existence d'une relation d'équilibre à long terme entre les prix du pétrole et les dépenses publiques, ce qui signifie que les dépenses publiques en Algérie sont étroitement liées aux variations des prix du pétrole à long terme. Cette relation étant à la fois causale et significative, la politique de dépenses publiques en Algérie s'étend dans les périodes de hausse des prix du pétrole et se contracte lorsque les prix du pétrole baissent à long terme. À court terme, il existe une relation causale significative entre les prix du pétrole et les dépenses publiques.
Keywords: Keywords: oil; oil prices; oil markets; government spending; public revenues.; الكلمات المفتاحية:النفط، أسعار النفط، أسواق النفط، الانفاق العام; الإيرادات العامة.; Mots-clés : pétrole; prix du pétrole; marchés pétroliers; dépenses publiques; revenus publics